The Effect of Growth Temperature and pH on Lipid Production of Mucor irregularis JR 1.1 for Potential Biodiesel Applications - Anggi Putri Pertiwi; Ilmi, Miftahul (Biota, 2026)
Mucor irregularis JR 1.1 is a filamentous fungus that can produce lipids. The lipids produced by M. irregularis JR 1.1 reach 40-60%, so they can be used as raw material for biodiesel. Temperature and pH are important factors that support M. irregularis JR 1.1 lipid production. Optimum temperature and pH enhance the activity of enzymes involved in lipid production.  Based on previous research, the optimization of temperature and pH in the lipid production of M. irregularis JR 1.1 has not been determined. Therefore, this study aims to determine the optimal temperature and pH for lipid production by M. irregularis JR 1.1. The study involved varying temperature and pH treatments using Response Surface Methodology (RSM). Subsequently, lipid production was performed at the optimum temperature and pH under different incubation times. Based on the research results, the highest biomass production was observed at 35°C and pH 4, the highest lipid production was at 35°C and pH 5.5, and the highest glucose consumption rate was at a temperature of 23°C and pH 5.5. The highest lipid yield percentage was 6.2%, and the highest production rate was 0.011g/L/hour at the 96th hour of incubation. Statistical analysis showed high significance, with R² values of 95.88% for lipid production and 89.98% for biomass yield. These findings suggest that M. irregularis JR 1.1 has promising potential as a microbial lipid source for sustainable biodiesel production, particularly under optimized culture conditions.